Estudo da cinetica de extração dos glicosideos da Stevia rebaudiana Bertoni com mistura CO2 + agua - Yoda, Simone Keiko (2001)
Orientadores: Maria Angela de Almeida Meireles, Marcia Ortiz Mayo Marques